ANALYZING THE HIGH RISE STRUCTURE WITH LATERAL LOADS - Pagade, Rahul Ramdas; D. B. Mohite (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Multi-storey building requirements are increasing day by day. There are various different new technologies which are developed regarding construction technique, material, type of system and analysis and design. Recently, the diagrid structural system has been widely used for tall buildings due to structural efficiency and aesthetic potential provided by triangulation of the system. Diagrid structures for tall buildings are very popular among engineers and architects. It is one of the evocative structural design solutions for sustainable tall buildings which are embraced by the diagrid structural scheme. In this paper, a thirty five storey residential diagrid structure with plan size 22.5 m × 21.65 m located in seismic zone III is considered for analysis. ETABS software is used for modelling and the analysis of seismic performance of typical diagrid structures was investigated. All structural members are designed as per IS 456: 2000 and load combinations of seismic forces are considered as per IS 1893 (Part I) 2016. Diagrid structures with various slopes of external braces were designed and their seismic performances were evaluated using dynamic linear method that is response spectrum method. A normal R.C.C frame residential structure is designed with the same designed loads and their seismic performance were evaluated. The comparison done on various parameters like base shear, story shear, top story displacement, time period and storey drift are plotted graphically to study the pattern of variation in diagrid structures with various slopes of external braces and normal frame structure. In diagrid structure, the major portion of lateral load is taken by external diagonal members who in turn release the lateral load in inner columns. It also concludes optimum diagrid angle for economical design and aspect ratio for the use of diagrid in case of residential buildings.